Evaluating Drought tolerance indices for selection of drought tolerant Orange Fleshed Sweet Potato (OFSP) genotypes in Ethiopia - Selamawit Abebe Gitore; Benjamin Danga; Sylvia Henga; Fekadu Gurmu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The purposes of this study were to assess the effectiveness of drought tolerance indices for selection of drought tolerance in orange fleshed sweet potato genotypes. In order to assess efficiency of drought tolerance indices, 10 Orange Fleshed Sweet Potato genotypes (OFSP) were evaluated under Normal or full irrigation and extreme water stress environments. A total of 9 drought tolerance indices including Stress tolerance index (STI), Tolerance (TOL), Mean Productivity (MP), Geometric Mean Productivity (GMP), Stress Susceptibility Index (SSI) Yield Index (YI), Yield Stability Index (YSI), Harmonic Mean (HM), and Stress Intensity Index (SII) were calculated based on yield obtained from the two moisture regimes. Rank mean, standard deviation of ranks and rank sum were calculated to identify well-performed varieties according to all indices. These STI, GMP, YI, SII and TOL showed high and significant correlation under both (Yp) and (Ys) condition. In consideration of all indices a variety MUSG014065-21-13, MUSG014065-21-14, and MUSG014019-7-50 exhibited the best mean of ranks and almost low standard deviation of rank. Among 10 genotypes, the combination of nine drought indices and deviation identified MUSG014065-21-13, MUSG014065-21-14, and MUSG014019-7-50 as a three promising and drought tolerant genotypes.